KOMUNIKASI ANTAR PERSONAL DALAM MEMBANGUN KELUARGA HARMONI - Rafi’i, Rafi’i (Penerbit Widina, Widina Media Utama, 2023)
Problems often occur in the family, such as frequent misunderstandings in interpreting messages sent from husband and wife. This misunderstanding can be caused by self-credibility, including messages that are not sufficient to carry complete trust. The only way that can build a bridge so that it is well-knit so as to create a harmonious family is to use the theory of interpersonal communication as a foundation; and research design using descriptive qualitative method. As a result, harmonious family communication can be realized through three important things; there is mutual trust, mutual respect, and mutual openness.ABSTRAKPersoalan kerap terjadi dalam keluarga seperti sering terjadinya kesalah pahaman dalam menafsirkan pesan yang tersempaikan dari pasangan suami-istri. Kesalah pahaman tersebut bisa disebabkan kredibelitas diri termasuk pesan yang tidak cukup membawa kepercayaan secara utuh. Satu-satunya jalan yang dapat menjembatani sehingga terjalin dengan baik sehingga tercipta keluarga harmoni adalah menggunakan teori komunikasi antar personal sebagai landasan; serta rancangan penelitian menggunakan metode kualitatif deskriptif. Alhasil komunikasi keluarga harmoni dapat terwujud melalui tiga hal penting; adanya sikap saling percaya, saling menghargai, dan saling terbuka.